Administrative encounters in general practice: low value or hidden value care?. Issue 3 (19th February 2018) - Trevena, Lyndal J; Harrison, Christopher; Britt, Helena C
Abstract: Objective: To determine the frequency of general practice administrative encounters, and to determine whether they represent low value care. Design: Secondary analysis of data from the Bettering Evaluation and Care of Health (BEACH) dataset. Setting: 1 568 100 GP–patient encounters in Australia, 2000–01 to 2015–16. Participants: An annual nationally representative random sample of about 1000 GPs, who each recorded the details of 100 consecutive encounters with patients. Main outcome measures: Proportions of general practice encounters that were potentially low value care encounters (among the patient's reasons for the encounter was at least one administrative, medication, or referral request) and potentially low value care only encounters (such reasons were the sole reason for the encounter). For 2015–16, we also examined other health care provided by GPs at these encounters. Results: During 2015–16, 18.5% (95% CI, 17.7–19.3%) of 97 398 GP–patient encounters were potentially low value care request encounters; 7.4% (95% CI, 7.0–7.9%) were potentially low value care only encounters. Administrative work was requested at 3.8% (95% CI, 3.5–4.0%) of GP visits, 35.4% of which were for care planning and coordination, 33.5% for certification, and 31.2% for other reasons. Medication requests were made at 13.1% (95% CI, 12.4–13.7%) of encounters; other health care was provided at 57.9% of medication request encounters, counselling, advice or education at 23.4%, and pathology testing was ordered at 16.7%. Referrals were requested at 2.8% (95% CI, 1.7–3.0%) of visits, at 69.4% of which additional health care was provided. The problems managed most frequently at potentially low value care only encounters were chronic diseases. Conclusion: Most patients requested certificates, medications and referrals in the context of seeking help for other health needs. Additional health care, particularly for chronic diseases, was provided at most GP administrative encounters. The MBS Review should consider the hidden value of these encounters.